2018
DOI: 10.1371/journal.pgen.1007251
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous termination of replication of the two chromosomes is an evolutionary selected feature in Vibrionaceae

Abstract: Vibrio cholerae, the causative agent of the cholera disease, is commonly used as a model organism for the study of bacteria with multipartite genomes. Its two chromosomes of different sizes initiate their DNA replication at distinct time points in the cell cycle and terminate in synchrony. In this study, the time-delayed start of Chr2 was verified in a synchronized cell population. This replication pattern suggests two possible regulation mechanisms for other Vibrio species with different sized secondary chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 74 publications
2
55
0
Order By: Relevance
“…In a previous study, we have used SHX‐based induction of stringent response to synchronize V. cholerae populations with respect to DNA replication (Kemter et al , ). We had found that V. cholerae cells contain fully replicated chromosomes after prolonged SHX treatment similar to what was observed for E. coli (Ferullo and Lovett, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study, we have used SHX‐based induction of stringent response to synchronize V. cholerae populations with respect to DNA replication (Kemter et al , ). We had found that V. cholerae cells contain fully replicated chromosomes after prolonged SHX treatment similar to what was observed for E. coli (Ferullo and Lovett, ).…”
Section: Resultsmentioning
confidence: 99%
“…The position of the crtS downstream of ori1 causes both chromosomes to terminate DNA replication at approximately the same time. This termination synchrony is conserved among the Vibrionaceae (Kemter et al , ). In order to reach cell doubling times shorter than the DNA replication phase during fast growth, V. cholerae can grow with overlapping DNA replication cycles, and therefore, initiate DNA replication before the ongoing round of DNA replication is finished (Stokke et al , ).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“… The 5′ but not the 3′ end of crtS is critical for its function. (A) The 153 bp crtS sequence from V. cholerae overlaid with a WebLogo ( Crooks et al, 2004 ), generated from different Vibrio species showing varied conservation along the length of the sequence, as in Kemter et al (2018) . Gray highlighted sequence denotes the minimal 70-bp that retain copy-number enhancement function of crtS in E. coli.…”
Section: Resultsmentioning
confidence: 99%
“…The structure and function of crtS are fairly well conserved in the Vibrionaceae family ( Kemter et al, 2018 ). The size of crtS (∼153-bp) is rather large for a protein binding site and is much larger than the RctB binding sites in the Chr2 replication origin (12-mers and 39-mers).…”
Section: Introductionmentioning
confidence: 99%